Novel alanines bearing an heteroaromatic side chain: synthesis and studies on fluorescent chemosensing of metals cations with biological relevance - Ferreira, Rosa Cristina Moutinho (2018)
A family of novel thienyl-benzoxazol-5-yl-L-alanines, consisting of an alanine core bearing a benzoxazole at the side chain with a thiophene ring at position 2, substituted with different (hetero)aryl substituents, was synthesised in order to study the tuning of the photophysical and chemosensory properties of the resulting compounds. These novel heterocyclic alanines and a series of structurally related bis-thienyl-benzoxazolyl-alanines 3g-j were evaluated for the first time in the recognition of selected metal cations with environmental, medicinal and analytical interest such as Co2+, Cu2+, Zn2+ and Ni2+, in acetonitrile solution, with the heterocycles at the side chain acting simultaneously as the coordinating and reporting units, via fluorescence changes. This behaviour can be explained by the involvement of the electron donor heteroatoms in the recognition event, through complexation of the metal cations. The spectrofluorimetric titrations showed that thienyl-benzoxazolyl-alanines 3a-j and 4a,b were non-selective fluorimetric chemosensors for the above mentioned cations, with the best results being obtained for the interaction of Cu2+ with bis-alanine 3j and deprotected alanines 4a,b. The encouraging photophysical and metal ion sensing properties of these thienyl-benzoxazolyl-alanines suggest that they can be used to obtain bioinspired fluorescent reporters for metal ion such as peptides/proteins with chemosensory/probing ability.